2021
DOI: 10.1107/s1600576721001138
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle neutron scattering measurements of mixtures of hydrogenous and deuterated n-tetradecane

Abstract: Small-angle neutron scattering (SANS) measurements on mixtures of hydrogenous and deuterated species can be used to determine the distribution of molecules in these blends. The molecules are isotopically distinguishable but are chemically identical. This approach has been applied with great success to polymer science, but fewer examples are available for small molecules, such as solvents. SANS measurements of combinations of the linear alkane n-tetradecane were performed on mixtures prepared at different volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…17 Similarly, there is no latent, broad small-angle scattering structure, as has been observed for liquids containing small nanosegregated regions, which is common in ILs, 49,50 and has also been seen in systems which are conventionally considered as homo- geneous, such as tetradecane, where a radius of gyration (R g ) can be elucidated by isotopic labelling of H-tetradecane : d 30tetradecane mixtures. 51 The only other signal observed was an experimental artefact at ca. 0.015 Å −1 for some 0w samples, which we assign to the short collection time, which causes issues because of the intrinsically low signal : noise ratio at low-Q on this instrument; this is seen in several measurements.…”
Section: Resultsmentioning
confidence: 96%
“…17 Similarly, there is no latent, broad small-angle scattering structure, as has been observed for liquids containing small nanosegregated regions, which is common in ILs, 49,50 and has also been seen in systems which are conventionally considered as homo- geneous, such as tetradecane, where a radius of gyration (R g ) can be elucidated by isotopic labelling of H-tetradecane : d 30tetradecane mixtures. 51 The only other signal observed was an experimental artefact at ca. 0.015 Å −1 for some 0w samples, which we assign to the short collection time, which causes issues because of the intrinsically low signal : noise ratio at low-Q on this instrument; this is seen in several measurements.…”
Section: Resultsmentioning
confidence: 96%
“…However, experiments carried out by Smith and Pre ´vost on mixtures of hydrogenated and deuterated tetradecane may provide an explanation for the source of this scattering. 49 They found that although no aggregates form in this system, scattering objects with a radius of gyration of around 5 Å were present. This can be understood by considering that in these mixtures there is contrast between the hydrogenated and deuterated alkane molecules resulting in distinct scattering objects at the molecular length scale, without the need for aggregation of any component.…”
Section: Sans Of Binary Mixtures Of [Cmentioning
confidence: 83%
“…Debye’s expression (eq ) was therefore used to fit the 2-EHL scattering data as flexible Gaussian polymer chains, with the corresponding fitted parameters shown in Table . This methodology has been successfully applied before by Arleth and Pedersen to decane and isooctane systems and subsequently by Smith and Prevost to C 14 H 30 /C 14 D 30 mixtures . The simple Debye model, with relatively few free fitting parameters, appears to represent a better fit to such systems than the random phase approximation (RPA).…”
Section: Resultsmentioning
confidence: 99%
“…In other words, 2-EHL can be treated using the same framework as a compact molecular version of linear Gaussian polymer chains, with 2 “Kuhn-type” subunits, which are freely able to rotate and gyrate with respect to the other, without any energetic penalty. Surprisingly, this is only slightly smaller than L K for some classic polymers, such as polydimethylsiloxane (PDMS) or polyethylene (PE), where L K = 15.6 and 15.4 Å, respectively, but is larger than that calculated for dodecane (8.9 Å) Figure a shows the Kuhn segment interpretation of 2-EHL structuring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation